A comparative study between hydrocolloid dressing and conventional vaseline gauze dressing in healing of donor site wound in split skin graft - K., Supreeth; R., Bhoomika (International Surgery Journal, 2025)
Background: One of the frequently performed procedures by plastic surgeons, and general surgeons is skin graft. Pain in the donor region is a typical patient complaint. Paraffin dressing usually covers the area of the skin graft donor location. Split-skin grafting is commonly used by surgeons to treat skin abnormalities in the event of ulcers, deep burns and subsequent trauma. Epidermis harvesting and upper 1/3rd of dermis resulting in a wound called donor site wound (DSW) are needed for the technique of split-skin graft harvesting. These wounds pose a sort of burden to patients during the procedure and after the wound healing process. These injuries tend to cause immense discomfort, are at risk of infection, and may cause scratching of the patient (pruritus) and cosmetic inconvenience. Care and management of local donor site wound (DSW) should aim to create an environment that promotes early epithelialization for the patient with shortened hospital stay period with minimal pain and discomfort. This study was done to evaluate effectiveness of hydrocolloid dressing in comparison to paraffin gauze dressing in healing of split skin graft donor site wound, and in comparing the parameters like pain, pruritis, requirement of analgesics of donor site wound. Methods: The study was done on 50 patients, 25 as study group who received effectiveness of hydrocolloid dressing and 25 as paraffin gauze dressing. Results: Statistics proved that study group (hydrocolloid dressing) had lesser pain than control group (paraffin gauze dressing). Conclusions: The hydrocolloid dressing on skin graft donor area reduces pain in post-operative period.